Vertical Profile of DO, CO2, and pH For 24 Hours In Full KJA And Less KJA Areas In Koto Panjang Hydroelectric Reservoir Kampar Regency Riau Province - Arico Candra Tambunan; Tengku Dahril; Asmika Harnalin Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTThis research was conducted in December 2020 in Koto Panjang Hydroelectric Reservoir, Kampar Regency, Riau Province. Sampling was conducted in 2 stations, namely in full KJA area and less KJA area, each station consists of 3 sampling points. Sampling was done every 4 hours during 3 days. Sampling was conducted in 6 depths based on tranparency, namely surface, 2 Secchi depth , 4 Secchi depth, 10 Secchi depth, 20 Secchi depth, and the bottom of the lake. Result shown full KJA area the average DO range 1.64 – 7.11 mg/L, CO2 ranges from 6.21 – 27.08 mg/L, pH ranges from 5.20 – 6.73, temperatures range from 25 – 32°C and transparency 106 cm. While in less KJA area average concentration of DO ranges from 1.51 – 7.01 mg / L, CO2 ranges from 5.77 - 23.97 mg / L, the average pH ranges from 5.73 - 6.50, temperatures range from 24 - 32 ° C and transparency 118 cm.Two way anova test concentrate of DO, CO2, and pH in full KJA area and less KJA were not significantly different. Keywords: Profil Vertikal, Parameter Kualitas Air, KJA, Waduk PLTA Koto Panjang